New Challenges for Sustainable Rural Development in the 21st Century (part 1) - Lorber, Lučka (Journal for Geography, 2009)
This is a special issue of the Journal for Geography published at the occasion of the 17th Annual Colloquium of the IGU Commission on the Sustainability of Rural Systems entitled New Challenges for Sustainable Rural Development in the 21st Century, which took place from 13th to 18th July 2009 in Maribor, Slovenia. In this issue, experts from Brazil, Australia, India, Japan, Israel, France, Ireland, Austria, Romania, the Netherlands and Slovenia present, analyse and explain the diversity of ways to improve the quality of life in rural areas all over the world.